2010
DOI: 10.1007/s11663-010-9347-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Physical Modeling of Steel Flow in a Two-Strand Tundish for Different Casting Conditions

Abstract: This article presents computational and water model studies of the three-dimensional turbulent fluid flow in a two-strand tundish for steady-state and transient casting conditions. First, it presents the flow field measurements obtained at a 1:3-scale water model of the tundish with the particle-image velocimetry (PIV) method during steady-state casting. The PIV measurements were performed using the Reynolds-similarity criterion. Thereafter, numerical simulation is carried out with the computational fluid dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Present state of the CFD techniques allow to calculate the fluid flow in tundish with the satisfying accuracy. This is confirmed by a good agreement in flow fields predicted mathematically and measured by laser-optical method using water models (Braun et al, 2010). For turbulence modelling, the standard or realizable k-ε models are mostly used, rather than Reynolds Stress Model (RSM) or Large-Eddy Simulations (LES).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Present state of the CFD techniques allow to calculate the fluid flow in tundish with the satisfying accuracy. This is confirmed by a good agreement in flow fields predicted mathematically and measured by laser-optical method using water models (Braun et al, 2010). For turbulence modelling, the standard or realizable k-ε models are mostly used, rather than Reynolds Stress Model (RSM) or Large-Eddy Simulations (LES).…”
Section: Introductionmentioning
confidence: 67%
“…However some investigations (Solorio-Diaz et al, 2004;Hou & Zou, 2005) demonstrate that this model does not give sufficient results for all cases. Investigations with water model (Braun et al, 2010) has shown that the overall flow phenomena in the tundish is well described by steady-state numerical simulations using RANS equations combined with the realizable k-ε model from Shih et al (Shih et al, 1995). This model is a good compromise between accuracy and simulation time.…”
Section: Numerical Modelling Of Non-metallic Inclusion Separation In mentioning
confidence: 99%
“…Physical modeling has played a key role in tundish research [4][5][6]. In physical modeling, a low temperature aqueous analog, generally water, is used to represent molten metal in a tundish.…”
Section: Of 10mentioning
confidence: 99%
“…The authors of papers [10,24,25,[49][50][51][52] apply average values of specific heat in modelling the continuous casting process. It seems to be a good trade-off when no experimental data is available.…”
Section: Material-related Parametersmentioning
confidence: 99%